2014
DOI: 10.5114/pg.2014.47894
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumour microenvironment in gastric cancer angiogenesis

Abstract: Gastric cancer is one of the most common cancers in the world. More than 95% of gastric cancers are adenocarcinomas originating from the glandular epithelium of the stomach lining. Unfortunately, a large number of patients are diagnosed when the tumour is at unresectable stage. Therefore, it is very important to understand the mechanisms involved in gastric cancer pathogenesis. One of them is angiogenesis, which means the formation of new blood vessels from pre-existing vasculature. This process is dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Despite advances in development of surgical therapy for gastric cancer (GC) and improvement in early diagnosis, the prognosis of metastatic GC is still poor, with a 5-year survival rate about only 3.1% in advanced GC patients [14]. Since most GC patients are diagnosed when the tumor is at an unresectable stage, early diagnosis of GC is crucial for treatment [15]. Studies showed that the NOB1 gene was associated with tumor development in various cancers such as ovarian cancer [16], laryngeal cancer [17], lung cancer [18], colorectal cancer [19], and gastric cancer [20] and could be a potential biomarker in predicting prognosis of lung cancer outcomes [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in development of surgical therapy for gastric cancer (GC) and improvement in early diagnosis, the prognosis of metastatic GC is still poor, with a 5-year survival rate about only 3.1% in advanced GC patients [14]. Since most GC patients are diagnosed when the tumor is at an unresectable stage, early diagnosis of GC is crucial for treatment [15]. Studies showed that the NOB1 gene was associated with tumor development in various cancers such as ovarian cancer [16], laryngeal cancer [17], lung cancer [18], colorectal cancer [19], and gastric cancer [20] and could be a potential biomarker in predicting prognosis of lung cancer outcomes [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node status is an independent prognostic factor in gastric cancer almost regardless of the staging method. But there are other prognostic factors such as T stage, M stage, vascular involvement, and histologic type of the tumour [ 26 , 27 ]. N status is also related to other factors because different incidences of LN metastases are observed in different T stages [ 27 ].…”
Section: Metastatic Lymph Nodes Are Not Independentmentioning
confidence: 99%
“…But there are other prognostic factors such as T stage, M stage, vascular involvement, and histologic type of the tumour [ 26 , 27 ]. N status is also related to other factors because different incidences of LN metastases are observed in different T stages [ 27 ]. On the other hand, metastasis to the specific LN stations may be correlated with the poor prognosis [ 28 ].…”
Section: Metastatic Lymph Nodes Are Not Independentmentioning
confidence: 99%
“…In preclinical models, anti-VEGF/VEGF receptor therapies show potent inhibition of angiogenesis and tumor growth [ 5 ]. In patients with gastric cancer, high VEGF levels are associated with increased tumor aggressiveness and reduced survival [ 6 ].…”
Section: Introductionmentioning
confidence: 99%